Dampak investasi sektor pertambangan terhadap pertumbuhan ekonomi dan tenaga kerja - Lestari, Diana (Faculty of Economics and Business Mulawarman University, 2016)
This study aims to assess the impact of investments in the mining sector and multiplication to economic growth and employment in the mining and quarrying sector in Indonesia during the period of last 15 years. Uses the secondary data from the Central Bureau of Statistics, the data were analyzed using simple linear regression. The study found a partial investment of mining and quarrying significant positive effect on economic growth. In this case means the first hypothesis stating the mining and quarrying sector investment positive effect on economic growth is accepted. As for economic growth significant positive effect on employment opportunities mining and quarrying sector. In this case means that the second hypothesis which states economic growth significant positive effect on employment is accepted mining and quarrying sector.Keyword: Investment, Economic Growth, Employment Opportunities, Mining and Quarrying, Indonesia